Penambahan ekstrak jenis tanaman herbal yang berbeda pada media pemeliharaan terhadap kelangsungan hidup benih ikan Nila (Oreochromis niloticus) - Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
The aim of this study was to know the herbal plants which effective to increase the survival of tilapia (Oreochromis niloticus) seed. The treatments of this experiment were addition of extract ciplukan leaf, sweet potato leaf, betel leaf, and without addition extract herbal as control. The results of this study showed that the use of extract of ciplukan leaf, and sweet potato leaf 5ml/L in rearing media during acclimatization could increase the survival of tilapia seed. Key words : Oreochromis niloticus, ciplukan leaf, sweet potato leaf, betel leaf, survival rate.